Alterations in Gene Expression and the Fatty Acid Profile Impact but Do Not Compromise the In Vitro Maturation of Zebrafish (Danio rerio) Stage III Ovarian Follicles after Cryopreservation - de Mello, Fernanda; Alonso, Daniel Jaen; Faria, Natália Pires Vieira Morais de; Marques, Victor Hugo; Oliveira, Ethiene Fernandes de [UNESP]; de Mello, Paulo Henrique; Godoy, Leandro César de; Moreira, Renata Guimaraes (MDPI, 2023)
The vitrification of ovarian follicles is a strategic tool that may contribute to advances in aquaculture and the conservation of many important species. Despite the difficulties inherent to the cryopreservation of oocytes, some successful protocols have been developed for different species, but little is known about the capacity of oocytes to develop after thawing. Therefore, the profiles of the reproductive pathway genes and fatty acid membrane composition during the initial stages of development were analyzed in fresh ovarian follicles and follicles after the vitrification process. There were differences in the expression of the hypothalamic–pituitary–gonad axis genes during the follicular development in the control group as well as in the vitrified group. Similarly, alterations in the composition of fatty acids were observed after vitrification. Despite this, many alterations were observed in the vitrified group; more than half of the stage III ovarian follicles were able to grow and mature in vitro. Therefore, the vitrification of ovarian follicles may impact them at molecular and membrane levels, but it does not compromise their capability for in vitro maturation, which indicates that the technique can be a strategic tool for aquaculture.
Keywords: aquaculture; fertility preservation; folliculogenesis; gamete quality; oogenesis; vitrification